Acute dermal effects of solar UV irradiation and efficacy of sunscreen use. Issue 1 (31st December 2022) - Lin, Yi-Chun; Chen, Yu-Chieh; Hwang, Bing-Fang; Chen, Chen-Peng
ABSTRACT: The Global Solar Ultraviolet (UV) Index provides limited information on health effects due to over-exposure. This study investigated the change in skin physiology in response to solar UV irradiation and the protective efficacy of a sunscreen. Fourteen female participants were divided into two groups, sunscreen users and non-users, and for 8 weeks they received solar irradiation and were monitored for change in the erythema-index (E-index), melanin-index, skin capillary blood flow, skin moisture, transepidermal water loss (TEWL), and skin temperature. The E-index and TEWL responded proportionally to solar radiation and could serve as indices of acute health effects from UV exposure. In the sun-radiated area, the E-index and TEWL measured on the forearm of the non-users were 111.3% and 138.4% of the levels determined for the users, respectively. Although thermal sensation and thermo-physiology were correlated, physiological monitoring was preferred over thermal sensation survey in evaluating the impact of solar UV irradiation.